216 Evaluation of child and adolescent mental health admissions to tertiary paediatric wards: an eating disorder focus. (17th August 2022) - Qalandari, Sadia; Cathie, Katrina; Williams, Sarah; Warren, Sarah
Abstract : Aims: 1. Review mental health (MH) conditions affecting children and young people (CYP) admitted to University Hospital Southampton (UHS) acute paediatric services between May 2019 – July 2021. 2. Gather CYP and carer's feedback on their inpatient experience when admitted with an Eating Disorder (ED). 3. Identify and suggest potential areas of improvement based on qualitative feedback obtained and consider future quality improvement. Methods: A service evaluation of: 1. Retrospective data from the CAMHS database analysed descriptively included reason for admission, length of stay (LOS), age and discharge location. 2. An inductive thematic analysis approach was used to analyse survey responses. Results: 808 patients age 11-18 were admitted for MH presentations across UHS with 49.3% presenting multiple times during the study period ( figure 1 ). The most common reason for initial presentation was overdose in 36.3% of admission. CYP with ED's had the longest median length of stay (LOS) of 8 days (IQR=0-15), with most other MH presentations having a median LOS of 1 day. Qualitative feedback surveys were sent to 37 parents and responses obtained from 9 CYP and 14 parent/carer's ( figure 1 ). 93% of parent/carer's and 78% of CYP felt they were listened to ( figure 2 ). The responses identified 6 main themes: (1) early, holistic, and individualised care; (2) knowledge and experience of EDs amongst various professionals; (3) partnership between the service, patient, and their families; (4) providing support for parent/carers; (5) potential improvements; and (6) external barriers to the care and support of the patient. These themes led to 2 main areas identified for improvement: education of ward-based staff who are not part of the ED team, including nurses, health care assistants and domestic staff serving meals to patients and earlier/increased psychological support for CYP and their parent/carer's. Conclusion: A positive experience was reported by most CYP and their parent/carer's. Nevertheless, our data suggests that improvements are required to provide more holistic care. Recommended improvements include providing training for all staff and enhancing psychological support, in particular support for parents/carer's.